2018
DOI: 10.1016/j.fm.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic identification of Penicillia and Aspergilli isolated from Italian grana cheese

Abstract: Penicillium and Aspergillus genera, both including mycotoxin producing species, were reported as associated to cheese and cheese working environment, but never studied in an extensive way in Italian grana cheese (Grana Padano and Parmigiano Reggiano). The aim of this work was to address the identification of Aspergilli and Penicillia associated to grana cheese in order to lay down the basis for risk assessment and safe processing for a high quality production. One hundred and four strains belonging to Aspergil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) (Decontardi et al, 2018;González et al, 2017;Garcia et al, 2018). As for the P. glabrum clade, our data corroborates Barreto et al (2011) and Houbraken et al (2014) that indicated high intra-specific β-tubulin variation for this group.…”
Section: Mycobiota Isolation and Identificationsupporting
confidence: 86%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) (Decontardi et al, 2018;González et al, 2017;Garcia et al, 2018). As for the P. glabrum clade, our data corroborates Barreto et al (2011) and Houbraken et al (2014) that indicated high intra-specific β-tubulin variation for this group.…”
Section: Mycobiota Isolation and Identificationsupporting
confidence: 86%
“…is reported as the dominant fungal genus growing on cheese [4]. Information about penicillia growing on grana cheese during ripening has been reported by Decontardi et al [10,12]. In particular, P. crustosum and P. solitum were the dominant species isolated, but other mycotoxin producing fungi identified were A. flavus and P. verrucosum.…”
Section: Of 14mentioning
confidence: 91%
“…A. versicolor CBS 108959 was later identified as A. jensenii by Decontardi et al[12] but A. versicolor will be kept in the text to remain consistent with the CBS website database labelling.…”
mentioning
confidence: 99%
“…Penicillium solitum was also detected in the Golot cheese samples in our study. Although P. solitum inhabits mainly fruits , the species has also been detected in various cheeses (Anelli et al, 2019;Decontardi et al, 2018;Ramos-Pereira et al, 2019) and meat products (Merla et al, 2018, Pleadin et al, 2017Scaramuzza et al, 2015). This species has not only been isolated from the product, but also from the air itself in the production plants (Scaramuzza et al, 2015), which indicates that air is one of the contamination routes.…”
Section: European Journal Of Science and Technology E-issn: 2148-2683mentioning
confidence: 99%